2022
DOI: 10.1108/ccsm-06-2021-0107
|View full text |Cite
|
Sign up to set email alerts
|

Collectivistic norms, beliefs and Mexican OCBs: gender and generation differences

Abstract: PurposeThe authors study the role of collectivistic norms and beliefs on organizational citizenship behaviors (OCBs) in Mexico, including differences across gender and generations.Design/methodology/approachThe authors researched the relationship between Mexican employees' collectivistic norms and beliefs and their OCBs, which the authors grouped into etic (universal), emic (regional) and unique (indigenous) categories, the latter referred to as Mexican OCBs (MOCBs). The authors also studied the role of gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 120 publications
(147 reference statements)
0
5
0
Order By: Relevance
“…The notion of organizational citizenship is influenced by the concept of extracurricular activities suggested by Katz (1964). OCBs are non-essential behaviors for the job, including showing consideration for other staff members and being considerate of co-workers and the organization (Baeza et al, 2022;Jayaweera et al, 2021). In informal organizations, this voluntary, spontaneous, and contributing behavior is the result of personal initiative, and exceeds the organization's contractual obligations (Choi and Sy, 2010).…”
Section: Moderating Role Of Organizational Citizenship Behavior (Ocb)mentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of organizational citizenship is influenced by the concept of extracurricular activities suggested by Katz (1964). OCBs are non-essential behaviors for the job, including showing consideration for other staff members and being considerate of co-workers and the organization (Baeza et al, 2022;Jayaweera et al, 2021). In informal organizations, this voluntary, spontaneous, and contributing behavior is the result of personal initiative, and exceeds the organization's contractual obligations (Choi and Sy, 2010).…”
Section: Moderating Role Of Organizational Citizenship Behavior (Ocb)mentioning
confidence: 99%
“…The notion of organizational citizenship is influenced by the concept of extracurricular activities suggested by Katz (1964). OCBs are non-essential behaviors for the job, including showing consideration for other staff members and being considerate of co-workers and the organization (Baeza et al. , 2022; Jayaweera et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…First, this scale can help human resource practitioners identify OCBCs in their organizations. Managers need to adjust to the new human resources approach that welcomes diversity (Yu et al, 2022;Baeza et al, 2022). Despite the importance of OCBs to organizational effectiveness, encouraging employee expressions of OCBs remains a challenge for HR managers (Rurkkhum & Bartlett, 2018, p. 108).…”
Section: Contributions and Managerial Implicationsmentioning
confidence: 99%
“…Stedham and Yamamura, 2004). Indeed, recent studies have shown that this dimension is crucial to understanding the role of culture in group performance in the workplace (Baeza et al, 2022;Staples and Zhao, 2006) because it influences members' appraisal of collective and personal benefits as well as their capacity to work interdependently on collaborative tasks. Along with individualism-collectivism, power distance is key to group performance, as it allows us to explain different group members' attitudes about gender roles and beliefs in power dynamics (Szymanowicz and Furnham, 2013), which may ultimately affect the effectiveness of collaborative learning groups (Cole et al, 2013) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Stedham and Yamamura, 2004). Indeed, recent studies have shown that this dimension is crucial to understanding the role of culture in group performance in the workplace (Baeza et al. , 2022; Staples and Zhao, 2006) because it influences members' appraisal of collective and personal benefits as well as their capacity to work interdependently on collaborative tasks.…”
Section: Introductionmentioning
confidence: 99%